1983
DOI: 10.1016/0014-5793(83)80786-8
|View full text |Cite
|
Sign up to set email alerts
|

Sites of cytochromeb‐563 reduction, and the mode of action of DNP‐INT and DBMIB in the chloroplast cytochromeb‐563/fcomplex

Abstract: When ferredoxin is the reductant of cytochrome b-563 in the chloroplast cytochrome b-563/f complex, the reaction rate varies with pH in a manner which permits identification of a plastoquinone/plastosemiquinone couple as an intermediate in the reaction. The requirement for the inhibitor, DNP-INT, in this reaction, suggests that there are two sites in the complex where plastosemiquinone can react with cytochrome(s) b-563. The ineffectiveness of DBMIB in promotion of ferredoxin-mediated cytochrome b-563 reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…On the other hand, there are various reports showing that ferredoxin can reduce Cyt b6 in the dark (Arnon and Chain 1979;Telfer and Barber 1981;O'Keefe 1983) and, using isolated Cyt b6/f complexes, Lam and Malkin (1982) showed that this reduction is partially sensitive to antimycin A. The measured rates of Cyt b6 reduction by ferredoxin (O'Keefe 1983) are compatible with the cyclic electron-transport rates measured here, being approx. 10-30 times slower than the published rates of plastoquinone-plastocyanin oxidoreductase.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…On the other hand, there are various reports showing that ferredoxin can reduce Cyt b6 in the dark (Arnon and Chain 1979;Telfer and Barber 1981;O'Keefe 1983) and, using isolated Cyt b6/f complexes, Lam and Malkin (1982) showed that this reduction is partially sensitive to antimycin A. The measured rates of Cyt b6 reduction by ferredoxin (O'Keefe 1983) are compatible with the cyclic electron-transport rates measured here, being approx. 10-30 times slower than the published rates of plastoquinone-plastocyanin oxidoreductase.…”
Section: Discussionsupporting
confidence: 75%
“…Bendall 1982; Crofts and Wraight 1983;Hauska et al 1983;O'Keefe 1983) allow single electrons to enter the plastoquinone pool via Cyt b6. On the other hand, there are various reports showing that ferredoxin can reduce Cyt b6 in the dark (Arnon and Chain 1979;Telfer and Barber 1981;O'Keefe 1983) and, using isolated Cyt b6/f complexes, Lam and Malkin (1982) showed that this reduction is partially sensitive to antimycin A. The measured rates of Cyt b6 reduction by ferredoxin (O'Keefe 1983) are compatible with the cyclic electron-transport rates measured here, being approx.…”
Section: Discussionmentioning
confidence: 99%
“…NQNO (and HQNO) inhibits reduction of plastoquinone at the Qc site (Selak andWhitmarsh 1982, Jones andWhitmarsh 1985). DNP-INT is generally considered to be a non-redox active equivalent of DBMIB (Trebst 1980), although there are some clear cases where it functions differently (O'Keefe 1983, Lam 1984. Based on its combined ability to both slow the rate and stimulate the extent of the plastoquinol reduction of cytochrome b in the isolated complex (data not shown), DNP-INT may be functioning as an inhibitor of both the Qz and Qc site.…”
Section: Inhibitors Of the Cytochrome Bf Complexmentioning
confidence: 99%
“…In addition to the measurement of phosphorylation, this cycle can be measured in a number of ways, including the reduction of the cytochromesfand b6, the electrochromic shift, and the slow rereduction of P-700 ÷ (Slovacek and Hind 1977, Crowther and Hind 1980, Crowther et al 1983, Leegood et al 1983, Rurainski et al 1982. The main issue within the context of this review is how reducing equivalents from ferredoxin are introduced into the cytochrome bf complex, since some schemes suggest participation of reduced ferredoxin or ferredoxin:NADP reductase at, or near, the Qc site of the cytochrome bf complex (Crowther and Hind 1980, Chain 1982, O'Keefe 1983, Hartung and Trebst 1985, whereas others have proposed a mechanism for the two electron reduction of plastoquinone by PSI, effectively providing additional plastoquinol for the cytochrome bf complex (Hosler andYocum 1984, Moss andBendall 1984). Although not recognized as integral components of the cytochrome bf complex, the participation of other, as yet poorly characterized components which interact with cytochrome b6 during cyclic electron transfer, such as a c-type cytochrome (Lavergne 1983), an iron-sulfur protein (Bouges-Bocquet 1980), or an NADH dehydrogenase type protein cannot be ruled out (Meng et al 1986).…”
Section: Mechanism Of Cyclic Electron Transfermentioning
confidence: 99%
See 1 more Smart Citation